Digital Texts and Reading Comprehension in Elementary School: A Literature Review - Neva, Omar Alonso (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The information age has raised several challenges for education, but it has also presented opportunities for improving teaching practices. This article aims to review and analyze the progress made in research in English and Spanish from 2015 to 2020, regarding the use of digital texts for reading comprehension in elementary school. I use a mixed approach and a documentary methodology to carry out the systematic literature review of articles published in databases recognized between 2015 and 2020. The documentary corpus of 50 articles was organized in thematic fact sheets according to pre—established categories and statistical trends in the bibliographic production. The results show trends regarding the country, participants, method, types of digital text and technologies used, and coincidences or discordances of the results obtained in the understanding and aspects of reading. It is concluded that digital texts increase the motivation towards reading, facilitate reading comprehension and promote collaborative learning, however, in some cases, the results are limited or do not differ from physical texts.